Utilizing ChatGPT-3.5 to Assist Ophthalmologists in Clinical Decision-making - Samir Cayenne; Natalia Penaloza; Anne C. Chan; M.I. Tahashilder; Rodney C. Guiseppi; Touka Banaee (Journal of Ophthalmic & Vision Research)
Purpose: ChatGPT-3.5 has the potential to assist ophthalmologists by generating a differential diagnosis based on patient presentation. Methods: One hundred ocular pathologies were tested. Each pathology had two signs and two symptoms prompted into ChatGPT-3.5 through a clinical vignette template to generate a list of four preferentially ordered differential diagnoses, denoted as Method A. Thirty of the original 100 pathologies were further subcategorized into three groups of 10: cornea, retina, and neuroophthalmology. To assess whether additional clinical information affected the accuracy of results, these subcategories were again prompted into ChatGPT-3.5 with the same previous two signs and symptoms, along with additional risk factors of age, sex, and past medical history, denoted as Method B. A one-tailed Wilcoxon signed-rank test was performed to compare the accuracy between Methods A and B across each subcategory (significance indicated by P < 0.05). Results: ChatGPT-3.5 correctly diagnosed 51 out of 100 cases (51.00%) as its first differential diagnosis and 18 out of 100 cases (18.00%) as a differential other than its first diagnosis. However, 31 out of 100 cases (31.00%) were not included in the differential diagnosis list. Only the subcategory of neuro-ophthalmology showed a significant increase in accuracy (P = 0.01) when prompted with the additional risk factors (Method B) compared to only two signs and two symptoms (Method A). Conclusion: These results demonstrate that ChatGPT-3.5 may help assist clinicians in suggesting possible diagnoses based on varying complex clinical information. However, its accuracy is limited, and it cannot be utilized as a replacement for clinical decision-making.